Predictors of Cardiac Sparing in Deep Inspiration Breath-Hold for Patients With Left Sided Breast Cancer - Mkanna, Abbas; Mohamad, Osama; Ramia, Paul; Thebian, Ranim; Makki, Maha; Tamim, Hani; Jalbout, Wassim; Youssef, Bassem; Eid, Toufic; Geara, Fady; Shahine, Bilal; Zeidan, Youssef H. (Frontiers in Oncology, 2018)
The purpose of this study was to evaluate patient-related non-dosimetric predictors of cardiac sparing with the use of deep inspiration breath-hold (DIBH) in patients with left-sided breast cancer undergoing irradiation (RT). Material and Methods We retrospectively reviewed charts and treatment plans of one-hundred and three patients with left-sided breast cancer. All patients had both free-breathing (FB) and DIBH (with body surface tracking) plans available. Mean heart dose (MHD) and V4 (heart volume receiving at least 4 Gy) were extracted from dose volume histograms. Fisher’s exact and Chi-square tests were used to identify predictors of reductions in MHD and V4 after DIBH. Results One-hundred and three patients were identified and most underwent mastectomy. MHD and V4 decreased significantly in DIBH plans (0.74 ± 0.25 Gy vs. 1.72 ± 0.98 Gy, p < 0.0001 for MHD; 4 ± 4.98 cc vs. 20.79 ± 18.2 cc, p < 0.0001 for V4). Body mass index (BMI), smoking and timing of CT simulation (spring/winter vs. summer/fall) were significant predictors of reduction in MHD whereas BMI, field size, chemotherapy, axillary dissection, and timing of CT simulation predicted reduction in V4. On multivariate analysis, BMI and timing of CT simulation remained significant predictors of the heart-sparing effect of DIBH. Conclusions In the setting of limited resources, identifying patients who will benefit the most from DIBH is extremely important. Prior studies have identified multiple dosimetric predictors of cardiac sparing and hereby we identified new non-dosimetric factors such as BMI and timing of treatments.